LITERATURE STUDY: THE TEACHER'S ROLE IN RECOGNIZING STUDENTS' LEARNING STYLES IN KINDERGARTEN - Chaterine Nuzzahara Shakiila; Apit Fathurohman (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
This research is a literature study with descriptive qualitative research using library research to try to describe the role of teachers in recognizing students' learning styles in kindergarten. In this literature study research, the author uses various written sources such as articles, books, journals, and relevant documents in accordance with the studies in this study. Understanding and recognizing students' learning styles is one of the important things that teachers need to know. A teacher needs to recognize the learning styles of students in the classroom. Teachers play a very important role in classifying and analyzing differences in students' learning styles. This aims to build effective and creative learning in responding to the unique learning styles of diverse learners. Recognizing students' learning styles can make it easier for teachers to provide good and effective learning. Teachers who have recognized the learning styles of students are also easier to choose learning activities that are in accordance with the abilities of students, so that students will more easily receive information. There are three types of learning styles, namely visual learning styles, auditorial learning styles, and kinesthetic learning styles. Visual learning styles learn through what is seen through the sense of sight. The auditorial learning style learns through what is heard through the sense of hearing. Kinesthetic learning style learns through movement. Teachers play a role in providing learning activities that are in accordance with the learning styles of students by using various strategies and methods in learning activities.